(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Postmenopausal osteoporosis remains a major cause of fragility fractures, loss of independence, and increasing healthcare costs. The aim of this narrative review was to summarize current evidence-based approaches to diagnosis, risk stratification, and treatment of postmenopausal osteoporosis, and to discuss their applicability in Uzbekistan. Sources were searched in PubMed/MEDLINE, PubMed Central, and on the official websites of the Endocrine Society, the International Society for Clinical Densitometry (ISCD), the National Osteoporosis Guideline Group (NOGG), and FRAXplus as of March 18, 2026. The review included clinical guidelines, official position statements, pivotal randomized trials, and Uzbekistan-specific epidemiological data. Contemporary diagnosis should rely on clinical risk factors, DXA, FRAX-based risk estimation, and, in selected cases, trabecular bone score and vertebral fracture assessment. Laboratory evaluation is primarily required to exclude secondary causes of bone loss and to ensure safe treatment selection. Antiresorptive drugs remain the mainstay for women at high fracture risk, whereas early anabolic or dual-action treatment followed by antiresorptive consolidation is appropriate for women at very high risk. For Uzbekistan, key priorities include broader access to FRAX and DXA, improved fracture ascertainment, and avoidance of unplanned denosumab discontinuation.